2019
DOI: 10.1186/s12906-019-2681-7
|View full text |Cite
|
Sign up to set email alerts
|

The mycelium of the Trametes versicolor (Turkey tail) mushroom and its fermented substrate each show potent and complementary immune activating properties in vitro

Abstract: BackgroundThe medicinal mushroom Trametes versicolor (Tv, Turkey Tail) is often prepared for consumption as a powder from the fungal mycelium and the fermented substrate on which it grew. The goal for this study was to evaluate the immune-modulating properties of the mycelium versus the fermented substrate, to document whether an important part of the immune-activating effects resides in the metabolically fermented substrate.MethodsTv mycelium was cultured on rice flour. The mycelium and the fermented substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…On the other hand, a shift of the terpenome composition in G. lingzhi , G. tsugae , and G. leucocontextum might have led to the production of terpenes with beneficial properties for human health. This study also allowed us to identify a polyketide synthase complex involved in the synthesis of the antibacterial lantipeptide [ 71 ] in G. lucidum , G. leucocontextum , Trametes versicolor , and T. pubescens , likely explaining the use of formulations based on these fungi as antibiotics [ 10 , 72 , 73 , 74 ]. Besides, the large content of gene clusters encoding unknown biochemical function(s) were found in Polyporales species, especially G. australe , suggested an outstanding ability to synthesize a large set of secondary metabolites of yet unknown function.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a shift of the terpenome composition in G. lingzhi , G. tsugae , and G. leucocontextum might have led to the production of terpenes with beneficial properties for human health. This study also allowed us to identify a polyketide synthase complex involved in the synthesis of the antibacterial lantipeptide [ 71 ] in G. lucidum , G. leucocontextum , Trametes versicolor , and T. pubescens , likely explaining the use of formulations based on these fungi as antibiotics [ 10 , 72 , 73 , 74 ]. Besides, the large content of gene clusters encoding unknown biochemical function(s) were found in Polyporales species, especially G. australe , suggested an outstanding ability to synthesize a large set of secondary metabolites of yet unknown function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lycopene, a common mushroom constituent has been found toinhibits NF-κB signaling [84]. Research on edible mushrooms has demonstrated a variety of anti-inflammatory actions [85,86].…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific structural and maturation elements of fruiting bodies and mycelia, and potentially even the fermented substrate from which the prepared product may have been produced, impact effects. Variances involve the chemistry, bioactive fractions derived from them, and biological activity [ 2 , 17 , 26 ].…”
Section: Mushrooms As Prevention or Treatment For Covid-19mentioning
confidence: 99%